Trigeminal Neuralgia : A Comprehensive Guide - Park, Kwan; Cho, Kyung Rae (Springer Nature Singapore : Imprint: Springer, 2023)
This book is focused on surgical treatment in trigeminal neuralgia (TN). Though microvascular decompression (MVD) is definite treatment for medically uncontrollable TN, manual focused on the surgical treatments are rare. This book includes overall view of TN, from diagnosis to treatment, more focused on technical pearls on MVD for neurosurgeons. Essential information of anatomy and pathophysiology are provided. Main topics would be indications, surgical considerations, electrophysiological monitoring during MVD surgery and outcomes of surgery. Furthermore, other non-surgical peripheral block techniques, radiosurgery and recent updated techniques will be discussed. The main target of this book will be neurosurgeons, neurosurgical trainees and also other physicians who's in charge of patients suffering from neuralgic pains.